Method for improving compatibility of medium-speed setting agent and cement in sprayed concrete

By adjusting the aluminum-sulfur ratio of the cement-gypsum-accelerator system in sprayed concrete, the problem of difficult control of the compatibility of alkali-free liquid acement agent and cement is solved, and the optimization and stability of the sprayed concrete are achieved. in complex construction environments.

CN119241192APending Publication Date: 2025-01-03BEIJING UNIV OF CIVIL ENG & ARCHITECTURE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411390727.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the prior art, the compatibility between alkali-free liquid accelerator and cement is difficult to regulate, resulting in unstable performance of sprayed concrete and cannot meet the complex and changeable situations in construction.

Method used

By adding gypsum to the sprayed concrete, adjusting the aluminum-sulfur ratio in the cement-gypsum-accelerator system, optimizing the compatibility of the accelerator and cement, using the calculation formula N = (AlC3A + Alaccelerator) / (SO42-cement + SO42-gypsum + SO42-accelerator) controls the aluminum-sulfur ratio in the range of 0.38-0.56 to achieve compatibility optimization.

Benefits of technology

By quantitatively characterizing compatibility, the suitable cement varieties are quickly screened to ensure that the sprayed concrete has a short set time, high compressive strength and good rebound, and is suitable for complex construction environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005073598630000021
    Figure BDA0005073598630000021
  • Figure BDA0005073598630000061
    Figure BDA0005073598630000061
  • Figure BDA0005073598630000062
    Figure BDA0005073598630000062
Patent Text Reader

Abstract

The invention provides a method for improving the compatibility of a medium-speed coagulant and cement in sprayed concrete. The method comprises the following steps: supplementing gypsum into the preparation raw materials of the sprayed concrete, adjusting the ratio of the amount of substance of aluminum element to sulfate radical in a cement-gypsum-accelerator system in the preparation raw materials, and optimizing the compatibility of the accelerator and cement. The method provided by the invention can simply, efficiently and accurately improve the compatibility of the medium-speed coagulant and cement in sprayed concrete, thereby regulating and controlling the setting time, compressive strength and other mechanical properties of the sprayed concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to a method for improving the compatibility of an accelerator and cement in shotcrete. Background Art

[0002] Shotcrete is a kind of concrete that is made by mixing cement, aggregate, accelerator and other construction raw materials for spraying construction. It is mainly used in railway tunnels, mines and underground projects, and requires low rebound rate, short setting time and high compressive strength. Accelerator is the core admixture in shotcrete, which plays a key role in the setting speed and strength of shotcrete. Traditional alkaline accelerator can introduce a large amount of alkali, which increases the probability of alkali-aggregate reaction in the later stage of concrete and has an adverse effect on the durability of concrete; in addition, the concrete mixture added with alkaline accelerator has insufficient cohesion and large rebound, which affects the construction efficiency; alkaline accelerator will also cause great harm to the health of construction workers during the construction process. Although the listing of alkali-free liquid accelerator with aluminum sulfate as the main component has solved the adverse effects of alkaline accelerator, alkali-free accelerator still has many problems in construction, such as uneven performance, poor stability and poor adaptability with different cements. Therefore, it is particularly important to study the adaptability of alkali-free accelerator and cement.

[0003] The national standard GB / T 8075-2017 "Terms of Concrete Admixtures" defines compatibility as the ability of concrete raw materials to match each other and work together when used together. For shotcrete, good compatibility means that after adding the accelerator, the cement has a short setting time, small rebound, and no loss of strength after hardening.

[0004] Factors that affect the compatibility of cement and accelerators include the age of cement, clinker composition, content and type of mixed materials, different accelerating components in the accelerator (aluminum sulfate, sodium aluminate and potassium tetrahydroxyaluminate), and type and content of gypsum.

[0005] At present, the compatibility of cement and alkali-free liquid accelerator can be improved by improving the formula of alkali-free liquid accelerator to match the cement used. Patent CN110963736A discloses a nano-gel polymer aluminum type liquid alkali-free accelerator, which uses hydrothermally synthesized nano-hydrated calcium silicate gel as the early strength agent of the system. The nano-scale hydrated calcium silicate gel provides abundant nucleation sites, which can quickly promote the hydration of tricalcium silicate, thereby improving the early strength of cement.

[0006] Another way is to prepare special cement for shotcrete to match the alkali-free liquid accelerator. Patent CN108098841A discloses a cement specially used for shotcrete mixed with alkali-free liquid accelerator. The special cement for shotcrete is prepared by controlling the content of silicate cement clinker, silica fume, fly ash, high-density gypsum, hemihydrate gypsum, ferrous sulfate and red mud components in the cement. After adding the alkali-free accelerator, the cement of the shotcrete has the characteristics of short setting time, high early strength, high later strength retention rate and small rebound rate, which greatly improves the various performances of the shotcrete.

[0007] However, in real engineering practice, the composition of alkali-free liquid accelerator and cement changes with the supplier all the time, and the quality of products produced by various manufacturers is different. It is impossible to truly regulate the compatibility between cement and alkali-free liquid accelerator in time. Simply changing the formula of alkali-free accelerator and the composition of cement clinker cannot meet the complex and changeable conditions in construction. Therefore, it is particularly important to establish a method to improve the compatibility of accelerator and cement in shotcrete, so as to simply and efficiently regulate the performance of shotcrete. Summary of the invention

[0008] In order to solve one of the above-mentioned technical problems existing in the prior art, the present invention provides a method for improving the compatibility between accelerator and cement in shotcrete. In view of the compatibility problem between cement and accelerator in the on-site construction process of shotcrete, the aluminum and sulfate content in cement, accelerator and gypsum are comprehensively considered, and gypsum is added to adjust the aluminum-sulfur ratio in the "cement-gypsum-accelerator" system, thereby optimizing the compatibility between the accelerator and cement. At the same time, the present invention proposes a calculation formula for calculating the aluminum-sulfur ratio in the "cement-gypsum-accelerator" system, and through experimental verification, when the aluminum-sulfur ratio of the system is controlled in the range of 0.38-0.56, the compatibility between cement and accelerator is good.

[0009] The present invention adopts the following technical solution:

[0010] A method for improving the compatibility of an accelerator and cement in shotcrete, the method comprising:

[0011] By adding gypsum to the raw materials for preparing shotcrete, the molar ratio N of aluminum element and sulfate in the cement-gypsum-accelerator system in the raw materials is adjusted to optimize the compatibility of the accelerator and cement.

[0012] According to some embodiments of the present invention, the N value is calculated by the following formula:

[0013]

[0014] Among them, Al C3A It is the amount of aluminum in C3A (tricalcium aluminate) in cement, in mol;

[0015] Al accelerator It is the amount of aluminum in the accelerating agent, in mol;

[0016] SO4 2- cement It is the amount of sulfur in the sulfate ion in cement, in mol;

[0017] SO4 2- gypsum is the amount of sulfur in the sulfate ion in the added gypsum, in mol;

[0018] SO4 2- accelerator It is the amount of sulfur element in sulfate ion in the accelerator, in mol.

[0019] In the present invention, the above Al accelerator It can be determined based on the content of aluminum-containing accelerating components (such as aluminum sulfate, aluminum hydroxide, etc.) in the quick-setting agent.

[0020] In the present invention, the above SO4 2- accelerator It can be determined based on the content of sulfate-containing components in the accelerator, such as aluminum sulfate.

[0021] According to some embodiments of the present invention, in the method, the value of N is adjusted to 0.38 to 0.56. When the value of N is within this range, the compatibility of cement and accelerator can be optimized, and the performance of the prepared shotcrete (such as setting time and compressive strength) is optimal.

[0022] According to some embodiments of the present invention, the accelerating setting agent comprises an alkali-free liquid accelerating setting agent.

[0023] According to some embodiments of the present invention, in the raw materials for preparation, the mass of the accelerating setting agent is 5%-10% of the mass of the cement, for example, 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween. In some embodiments, in the raw materials for preparation, the mass of the accelerating setting agent is 5%-9% of the mass of the cement.

[0024] According to some embodiments of the present invention, when the N value in the raw material for preparing shotcrete is greater than 0.56, gypsum is added to the cement to adjust the N value to between 0.38 and 0.56.

[0025] According to some embodiments of the present invention, the gypsum includes, but is not limited to, one or more of dihydrate gypsum, hemihydrate gypsum, and anhydrous gypsum.

[0026] According to some embodiments of the present invention, the amount of gypsum added is 0.5%-10% of the mass of cement, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% or any value therebetween. In some embodiments, the amount of gypsum added is 1%-5.5% of the mass of cement.

[0027] According to some embodiments of the present invention, when the mass of the accelerator is 5%-6% of the mass of cement, preferably 5%-5.5%, the added amount of gypsum is 1%-3% of the mass of cement, for example, 1%, 1.5%, 2%, 2.5%, 3% or any value therebetween, preferably 0.5%-1.5%; this allows the accelerator to have good compatibility with cement, and the resulting shotcrete has a suitable setting time, good resilience and high compressive strength.

[0028] According to some embodiments of the present invention, when the mass of the accelerator is 6%-8%, preferably 6.5%-7.5%, of the mass of cement, the added amount of gypsum is 1%-4%, for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or any value therebetween, preferably 2.5%-3.5% of the mass of cement; in this way, the accelerator and cement have good compatibility, and the obtained shotcrete has suitable setting time, good resilience and high compressive strength.

[0029] According to some embodiments of the present invention, when the mass of the accelerator is 8%-10%, preferably 8.5%-9.5%, of the mass of cement, the added amount of gypsum is 2%-5.5% of the mass of cement, for example, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5% or any value therebetween, preferably 4.5%-5.5%; in this way, the accelerator and cement have good compatibility, and the obtained shotcrete has suitable setting time, good resilience and high compressive strength.

[0030] According to some embodiments of the invention, the cement comprises Portland cement.

[0031] According to some embodiments of the present invention, the properties of the shotcrete include setting time and compressive strength.

[0032] According to some embodiments of the present invention, the components of the accelerating setting agent include aluminum sulfate, a complexing agent and a pH regulator.

[0033] According to some embodiments of the present invention, the components of the accelerating setting agent further include fluoride; the fluoride includes but is not limited to: one or more of sodium fluoride, aluminum fluoride, magnesium fluorosilicate, and sodium chlorofluoroate.

[0034] According to some embodiments of the present invention, the components of the accelerating setting agent include aluminum sulfate, fluoride, a complexing agent and a pH adjuster.

[0035] In the present invention, the term "aluminum sulfate" refers to aluminum sulfate containing crystal water (such as aluminum sulfate 18hydrate), anhydrous aluminum sulfate or a mixture thereof.

[0036] In the present invention, the complexing agent includes an alcohol amine, for example, one or more of diethanolamine, triethanolamine, and triisopropanolamine. In some embodiments, the complexing agent includes diethanolamine.

[0037] In the present invention, the pH adjuster includes an inorganic acid and / or an organic acid, for example, one or more of oxalic acid, lactic acid, phosphoric acid, citric acid, malic acid, ascorbic acid, and salicylic acid. In some embodiments, the pH adjuster includes phosphoric acid.

[0038] In the present invention, the components of the accelerating setting agent also include a solvent, such as water.

[0039] According to some embodiments of the present invention, components of the accelerating setting agent include aluminum sulfate, diethanolamine and phosphoric acid.

[0040] According to some embodiments of the present invention, components of the accelerating setting agent include aluminum sulfate, fluoride, diethanolamine and phosphoric acid.

[0041] According to some embodiments of the present invention, components of the accelerating setting agent include aluminum sulfate, sodium fluoride, diethanolamine and phosphoric acid.

[0042] According to some embodiments of the present invention, the mass percentage of aluminum sulfate in the accelerator is 30-50%, for example, 30%, 35%, 38%, 40%, 42%, 45%, 48%, 50% or any value therebetween, preferably 35-40%.

[0043] According to some embodiments of the present invention, the mass percentage of fluoride in the accelerating setting agent is 0-1.0%, for example, 0, 0.1%, 0.2%, 0.5%, 0.8%, 1.0% or any value therebetween, preferably 0 or 0.1-0.5%.

[0044] According to some embodiments of the present invention, in the accelerating agent, the mass percentage of the complexing agent is 15-30%, for example, 15%, 18%, 20%, 22%, 25%, 28%, 30% or any value therebetween, preferably 20-25%.

[0045] According to some embodiments of the present invention, in the accelerating setting agent, the mass percentage of the pH adjusting agent is 0.1-1.0%, for example, 0.1%, 0.2%, 0.5%, 0.8%, 1.0% or any value therebetween, preferably 0.5-1.0%.

[0046] According to some embodiments of the present invention, the mass percentage of the solvent is 30-50%, for example, 30%, 35%, 38%, 40%, 42%, 45%, 48%, 50% or any value therebetween, preferably 35-45%.

[0047] According to some embodiments of the present invention, the accelerating setting agent comprises, by weight percentage: 30-50% aluminum sulfate, 15-30% diethanolamine, 0.1-1.0% phosphoric acid, and 30-50% water.

[0048] According to some embodiments of the present invention, the accelerating setting agent comprises, by weight percentage: 35-40% aluminum sulfate, 20-25% diethanolamine, 0.5-1.0% phosphoric acid, and 35-45% water.

[0049] According to some embodiments of the present invention, the accelerating setting agent includes, by weight percentage: 30-50% aluminum sulfate, 0-1.0% sodium fluoride, 15-30% diethanolamine, 0.1-1.0% phosphoric acid, and 30-50% water.

[0050] According to some embodiments of the present invention, the accelerating setting agent includes, by weight percentage: 35-40% aluminum sulfate, 0.1-0.5% sodium fluoride, 20-25% diethanolamine, 0.5-1.0% phosphoric acid, and 35-45% water.

[0051] According to some embodiments of the present invention, the accelerating setting agent is prepared by a method comprising the following steps:

[0052] Mixing aluminum sulfate and the solvent and heating to obtain a suspension; preferably, the heating temperature is 50-80° C.;

[0053] The suspension is mixed with the complexing agent and then mixed with the pH regulator to obtain the accelerating setting agent.

[0054] According to some embodiments of the present invention, the accelerating setting agent is prepared by a method comprising the following steps:

[0055] Mixing aluminum sulfate, fluoride and the solvent and heating to obtain a suspension; preferably, the heating temperature is 50-80° C.;

[0056] The suspension is mixed with the complexing agent and then mixed with the pH regulator to obtain the accelerating setting agent.

[0057] Compared with the prior art, the present invention has the following beneficial effects:

[0058] (1) The present invention establishes an evaluation calculation formula (aluminum-sulfur ratio) for the compatibility between cement and accelerator, and the compatibility of the system can be directly characterized in a quantitative manner, which has the advantages of being simple to understand and convenient to calculate.

[0059] (2) The present invention takes the ideal aluminum-sulfur ratio of 0.38-0.56 as the standard. In actual engineering, especially in high-altitude and severe cold construction environments, the cement variety that best matches the quick-setting agent used in the project can be quickly screened out.

[0060] (3) When the type and dosage of the accelerator remain unchanged, a certain amount of gypsum can be added to the cement to adjust the aluminum-sulfur ratio so that it can achieve the optimal compatibility value with the accelerator used. DETAILED DESCRIPTION

[0061] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention.

[0062] The reagents used in the following experiments of the present invention, unless otherwise specified, are all conventional commercial products or reagents prepared by conventional methods, and the methods used in the experiments, unless otherwise specified, are all conventional experimental methods. The instruments used in the experiments, unless otherwise specified, can all be obtained through commercial channels.

[0063] In the present invention, the term "compatibility" refers to the ability of concrete raw materials to match each other and work together when used together. For shotcrete, good compatibility means that after adding the accelerator, the cement has a short setting time, small rebound, and no loss of strength after hardening.

[0064] The present invention has been found through research that the ratio of the amount of aluminum element and sulfate substance (sulfur-aluminum ratio) in the "accelerator-cement-gypsum" system is a key factor affecting the macroscopic performance of the system. Therefore, the compatibility of the accelerator and cement can be improved by adjusting the aluminum-sulfur ratio in the system, thereby optimizing the performance of the shotcrete. The present invention has been found through research that when the aluminum-sulfur ratio of the system is controlled in the range of 0.38-0.56, the compatibility of cement and the accelerator is optimal.

[0065] In the following embodiments of the present invention, the calculation formula of the aluminum-sulfur ratio in the "cement-accelerator-water" system is as follows:

[0066]

[0067] Among them, AlC3A is the amount of aluminum in C3A in cement, in mol;

[0068] Al accelerator It is the amount of aluminum in the accelerating agent, in mol;

[0069] SO4 2- cement It is the amount of sulfur in the sulfate ion in cement, in mol;

[0070] SO4 2- gypsum is the amount of sulfur in the sulfate ion in the added gypsum, in mol;

[0071] SO4 2- accelerator It is the amount of sulfur element in sulfate ion in the accelerator, in mol.

[0072] According to the above calculation formula, an evaluation method for the compatibility between cement and alkali-free liquid accelerator in the "cement-accelerator-gypsum" system was established. By controlling the aluminum-sulfur ratio at 0.38-0.56, the compatibility between cement and alkali-free liquid accelerator can be optimized, and the performance of shotcrete can be significantly optimized.

[0073] The "Esheng cement" used in the following experiments of the present invention is PO type 42.5 ordinary Portland cement, produced by Sichuan Esheng Cement Co., Ltd., and its chemical composition is: 0.17wt% Na2O, 0.87wt% MgO, 5.31wt% Al2O3, 21.89wt% SiO2, 2.56wt% SO3, 63.04wt% CaO, 4.24wt% Fe2O3; the mineral composition is: 53.87wt% C3S, 9.01wt% C2S, 6.27wt% C3A, 9.40wt% C4AF.

[0074] Example 1

[0075] 1) Self-made alkali-free liquid accelerating setting agent: The main component is aluminum sulfate, and the complexing agent is diethanolamine. Add 450 grams of aluminum sulfate 18hydrate to 480 milliliters of water, stir at a constant speed for 20 minutes in an environment of 60°C, and then stand for 0.5 hours to obtain a uniform suspension; slowly add 260 grams of diethanolamine to the suspension and stir at a constant speed for 0.5 hours, and finally add 10 grams of phosphoric acid and keep stirring at a constant speed for 2 hours to obtain the laboratory-made alkali-free liquid accelerating setting agent A-1.

[0076] 2) Different mass fractions of dihydrate gypsum (0, 1%, 3%, 5%, 7%, 9%) were added to the base cement and then tested with A-1 alkali-free liquid accelerator. The dosage of alkali-free liquid accelerator was fixed at 5%.

[0077] 3) When the dosage of A-1 alkali-free liquid accelerator is fixed at 5%, after adding different amounts of dihydrate gypsum, the calculated aluminum-sulfur ratio in the "cement-alkali-free liquid accelerator-water" system is shown in Table 1.

[0078] The setting time of cement paste and compressive strength of mortar were tested according to the method of "Accelerator for Shotcrete" (GB / T 35159-2017). The water-cement ratio of the cement paste was 0.35; the water-cement ratio of the mortar was 0.5, and the mortar-sand ratio was 1:1.5. The results are shown in Table 1.

[0079] Table 1

[0080]

[0081]

[0082] Example 2

[0083] 1) Prepare the alkali-free liquid quick-setting agent A-1 as in Example 1.

[0084] 2) Different mass fractions of dihydrate gypsum (0, 1%, 3%, 5%, 7%, 9%) were added to the reference cement and then tested with A-1 alkali-free liquid accelerator. The dosage of alkali-free liquid accelerator was fixed at 7%.

[0085] 3) When the dosage of A-1 alkali-free liquid accelerator is fixed at 7%, after adding different amounts of dihydrate gypsum, the calculated aluminum-sulfur ratio in the "cement-alkali-free liquid accelerator-water" system is shown in Table 2.

[0086] The setting time of cement paste and compressive strength of mortar were tested according to the method of "Accelerator for Shotcrete" (GB / T 35159-2017). The water-cement ratio of the cement paste was 0.35; the water-cement ratio of the mortar was 0.5, and the mortar-sand ratio was 1:1.5. The results are shown in Table 2.

[0087] Table 2

[0088]

[0089] Example 3

[0090] 1) Prepare the alkali-free liquid quick-setting agent A-1 as in Example 1.

[0091] 2) Different mass fractions of dihydrate gypsum (0, 1%, 3%, 5%, 7%, 9%) were added to the reference cement and then tested with A-1 alkali-free liquid accelerator. The dosage of alkali-free liquid accelerator was fixed at 9%.

[0092] 3) When the dosage of A-1 alkali-free liquid accelerator is fixed at 9%, after adding different amounts of dihydrate gypsum, the calculated aluminum-sulfur ratio in the "cement-alkali-free liquid accelerator-water" system is shown in Table 3.

[0093] The setting time of cement paste and compressive strength of mortar were tested according to the method of "Accelerator for Shotcrete" (GB / T 35159-2017). The water-cement ratio of the cement paste was 0.35; the water-cement ratio of the mortar was 0.5, and the mortar-sand ratio was 1:1.5. The results are shown in Table 3.

[0094] Table 3

[0095]

[0096] Conclusion 1: From the data in Tables 1-3, it can be seen that the alkali-free accelerators prepared in the laboratory in Examples 1-3 have different effects after being added to cement at 5%, 7%, and 9% of the mass of the benchmark cement, respectively.

[0097] As shown in Table 1, when the dosage of alkali-free liquid accelerating agent is 5%, 1% mass fraction of dihydrate gypsum is added to the base cement, and the aluminum-sulfur ratio is 0.56, the setting time of cement paste can be shortened, and the hardened mortar can achieve the highest compressive strength.

[0098] As shown in Table 2, when the dosage of alkali-free liquid accelerating agent is 7%, 3% mass fraction of dihydrate gypsum is added to the base cement, and the aluminum-sulfur ratio is 0.44, the setting time of cement paste can be shortened, and the hardened mortar can achieve the highest compressive strength.

[0099] As shown in Table 3, when the dosage of alkali-free liquid accelerator is 9%, 5% mass fraction of dihydrate gypsum is added to the base cement, and the aluminum-sulfur ratio is 0.38, the cement paste setting time can be the shortest, and the hardened mortar can achieve the highest compressive strength.

[0100] Example 4

[0101] (1) Prepare the alkali-free liquid quick-setting agent A-1 in the same manner as in Example 1.

[0102] (2) Different mass fractions of dihydrate gypsum (0, 1%, 3%, 5%, 7%, 9%) were added to Esheng cement, and then tested with A-1 alkali-free liquid accelerator. The dosage of alkali-free liquid accelerator was fixed at 5%.

[0103] (3) When the dosage of alkali-free liquid accelerating agent is kept constant at 5%, the aluminum-sulfur ratio calculated after adding different amounts of dihydrate gypsum is shown in Table 4.

[0104] The setting time of cement paste and compressive strength of mortar were tested according to the method of "Accelerator for Shotcrete" (GB / T 35159-2017). The water-cement ratio of the cement paste was 0.35; the water-cement ratio of the mortar was 0.5, and the mortar-sand ratio was 1:1.5. The results are shown in Table 4.

[0105] Table 4

[0106]

[0107]

[0108] Example 5

[0109] (1) Prepare the alkali-free liquid quick-setting agent A-1 in the same manner as in Example 1.

[0110] (2) Different mass fractions of dihydrate gypsum (0, 1%, 3%, 5%, 7%, 9%) were added to Esheng cement, and then tested with A-1 alkali-free liquid accelerator. The dosage of alkali-free liquid accelerator was fixed at 7%.

[0111] (3) When the dosage of alkali-free liquid accelerating agent is kept constant at 7%, the aluminum-sulfur ratio calculated after adding different amounts of dihydrate gypsum is shown in Table 5.

[0112] The setting time of cement paste and compressive strength of mortar were tested according to the method of "Accelerator for Shotcrete" (GB / T 35159-2017). The water-cement ratio of the cement paste was 0.35; the water-cement ratio of the mortar was 0.5, and the mortar-sand ratio was 1:1.5. The results are shown in Table 5.

[0113] Table 5

[0114]

[0115] Example 6

[0116] (1) Prepare the alkali-free liquid quick-setting agent A-1 in the same manner as in Example 1.

[0117] (2) Different mass fractions of dihydrate gypsum (0, 1%, 3%, 5%, 7%, 9%) were added to Esheng cement, and then tested with A-1 alkali-free liquid accelerator. The dosage of alkali-free liquid accelerator was fixed at 9%.

[0118] (3) When the dosage of alkali-free liquid accelerating agent is kept constant at 9%, the aluminum-sulfur ratio calculated after adding different amounts of dihydrate gypsum is shown in Table 6.

[0119] The setting time of cement paste and compressive strength of mortar were tested according to the method of "Accelerator for Shotcrete" (GB / T 35159-2017). The water-cement ratio of the cement paste was 0.35; the water-cement ratio of the mortar was 0.5, and the mortar-sand ratio was 1:1.5. The results are shown in Table 6.

[0120] Table 6

[0121]

[0122] Conclusion 2: From the data in Table 4-6, it can be seen that the strength effects of the laboratory-made alkali-free accelerator A-1 in comparative example 4-6 are different after being added to cement at 5%, 7% and 9% of the mass of Eshan cement respectively.

[0123] As shown in Table 4, when the dosage of alkali-free liquid accelerating agent is 5%, 1% mass fraction of dihydrate gypsum is added to the base cement, and the aluminum-sulfur ratio is 0.55, the setting time of cement paste can be minimized, and the hardened mortar can achieve the highest compressive strength.

[0124] As shown in Table 5, when the dosage of alkali-free liquid accelerator is 7%, 3% mass fraction of dihydrate gypsum is added to the base cement, and the aluminum-sulfur ratio is 0.45, the setting time of cement paste can be shortened, and the hardened mortar can achieve the highest compressive strength.

[0125] As shown in Table 6, when the dosage of alkali-free liquid accelerating agent is 9%, 5% mass fraction of dihydrate gypsum is added to the base cement, and the aluminum-sulfur ratio is 0.39, the setting time of cement paste can be the shortest, and the hardened mortar can achieve the highest compressive strength.

[0126] Example 7

[0127] (1) Self-made alkali-free liquid accelerating agent: The main ingredients are aluminum sulfate and sodium fluoride, and the complexing agent is diethanolamine. 450 g of aluminum sulfate 18hydrate and 4.5 g of sodium fluoride are added to 470 ml of water, stirred at a constant speed for 20 minutes in an environment of 60°C, and then allowed to stand for 0.5 hour to obtain a uniform suspension; 260 g of diethanolamine is slowly added to the suspension and stirred at a constant speed for 0.5 hour, and finally 10 g of phosphoric acid is added and stirred at a constant speed for 2 hours to obtain the laboratory-made alkali-free liquid accelerating agent A-2.

[0128] (2) Different mass fractions of dihydrate gypsum (0, 1%, 3%, 5%, 7%, 9%) were added to the base cement and then tested with A-1 alkali-free liquid accelerator. The dosage of alkali-free liquid accelerator was fixed at 9%.

[0129] (3) When the dosage of alkali-free liquid accelerating agent is kept constant at 9%, the aluminum-sulfur ratio calculated after adding different amounts of dihydrate gypsum is shown in Table 7.

[0130] The setting time of cement paste and compressive strength of mortar were tested according to the method of "Accelerator for Shotcrete" (GB / T 35159-2017). The water-cement ratio of the cement paste was 0.35; the water-cement ratio of the mortar was 0.5, and the mortar-sand ratio was 1:1.5. The results are shown in Table 7.

[0131] Table 7

[0132]

[0133] As shown in Table 7, when the dosage of alkali-free liquid accelerating agent is 9%, 5% mass fraction of dihydrate gypsum is added to the base cement, and the aluminum-sulfur ratio is 0.38, the setting time of cement paste can be the shortest, and the hardened mortar can achieve the highest compressive strength.

[0134] Based on the above results, it is shown that the calculation results are more accurate when the aluminum-sulfur ratio formula of the present invention is used. When the aluminum-sulfur ratio is 0.38-0.56, the setting time is the shortest and the compressive strength is the highest. It can be predicted that ordinary Portland cement can also achieve better performance effects in construction through the formula and evaluation method of the present invention, and is suitable for the design of the proportion of different cements and alkali-free quick-setting agents produced by different manufacturers under various complex conditions.

[0135] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.

Claims

1. A method for improving the compatibility of an accelerator and cement in shotcrete, characterized in that: The method comprises: adding gypsum to the raw materials for preparing shotcrete, adjusting the molar ratio N of aluminum element and sulfate radical in the cement-gypsum-accelerator system in the raw materials, and optimizing the compatibility of the accelerator and cement.

2. The method according to claim 1, characterized in that The N value is calculated by the following formula: Among them, Al C3A is the amount of aluminum in C3A in cement, in mol; Al accelerator It is the amount of aluminum in the accelerating agent, in mol; SO4 2- cement It is the amount of sulfur in the sulfate ion in cement, in mol; SO4 2- gypsum is the amount of sulfur in the sulfate ion in the added gypsum, in mol; SO4 2- accelerator It is the amount of sulfur element in sulfate ion in the accelerator, in mol.

3. The method according to claim 1 or 2, characterized in that: Adjust the value of N to 0.38~0.

56.

4. The method according to any one of claims 1 to 3, characterized in that: The accelerating setting agent comprises an alkali-free liquid accelerating setting agent; and / or, in the preparation raw materials, the mass of the accelerating setting agent is 5%-10% of the mass of the cement, preferably 5%-9%.

5. The method according to any one of claims 1 to 4, characterized in that: When the N value in the raw material for preparing shotcrete is greater than 0.56, gypsum is added to the cement to adjust the N value to between 0.38 and 0.

56.

6. The method according to any one of claims 1 to 5, characterized in that: The amount of gypsum added is 0.5%-10% of the mass of cement, preferably 1%-5.5%; Preferably, when the mass of the accelerating agent is 5%-6% of the mass of cement, preferably 5%-5.5%, the added amount of the gypsum is 1%-3% of the mass of cement, preferably 0.5%-1.5%; Preferably, when the mass of the accelerating agent is 6%-8% of the mass of cement, preferably 6.5%-7.5%, the added amount of the gypsum is 1%-4% of the mass of cement, preferably 2.5%-3.5%; Preferably, when the mass of the accelerating setting agent is 8%-10% of the mass of cement, preferably 8.5%-9.5%, the added amount of the gypsum is 2%-5.5% of the mass of cement, preferably 4.5%-5.5%.

7. The method according to any one of claims 1 to 6, characterized in that: The cement includes silicate cement; and / or the gypsum includes one or more of dihydrate gypsum, hemihydrate gypsum, and anhydrous gypsum.

8. The method according to any one of claims 1 to 7, characterized in that: The components of the accelerating setting agent include aluminum sulfate, a complexing agent and a pH adjusting agent; optionally, the components of the accelerating setting agent also include fluoride; the fluoride includes one or more of sodium fluoride, aluminum fluoride, magnesium fluorosilicate and sodium chlorofluoroate; Preferably, the complexing agent includes an alcohol amine, more preferably includes one or more of diethanolamine, triethanolamine, and triisopropanolamine, and further preferably includes diethanolamine; Preferably, the pH adjuster comprises an inorganic acid and / or an organic acid, more preferably comprises one or more of oxalic acid, lactic acid, phosphoric acid, citric acid, malic acid, ascorbic acid, and salicylic acid; further preferably comprises phosphoric acid; Preferably, the components of the quick-setting agent further include a solvent, and the solvent preferably includes water.

9. The method according to claim 8, characterized in that In the accelerating setting agent, the mass percentage of aluminum sulfate is 30-50%, preferably 35-40%; and / or the mass percentage of fluoride is 0-1.0%, preferably 0 or 0.1-0.5%; and / or the mass percentage of the complexing agent is 15-30%, preferably 20-25%; and / or the mass percentage of the pH adjusting agent is 0.1-1.0%, preferably 0.5-1.0%; and / or the mass percentage of the solvent is 30-50%, preferably 35-45%.

10. The method according to claim 8 or 9, characterized in that: The accelerating setting agent is prepared by a method comprising the following steps: Mixing aluminum sulfate, optional fluoride and the solvent and heating to obtain a suspension; preferably, the heating temperature is 50-80° C.; The suspension is mixed with the complexing agent and then mixed with the pH regulator to obtain the accelerating setting agent.